AS TÉCNICAS DA FASE DE ORGANIZAÇÃO DO PROCESSO: Aspectos nucleares - Col, Caio de Sa Dal (2022)
This dissertation aimed to investigate whether the transport of the process organization techniques, provided for in art. 357, of CPC/15, for phases and procedures other than the common procedure, where it is previously inserted, can efficiently assist in the realization of the constitutional values of the process and in the adequate treatment of conflicts. This object is closely linked to the Justice, Process and Constitution concentration area and the Process, Techniques and Protection of Existential and Patrimonial Rights research line of the Stricto Sensu Postgraduate Program in Procedural Law at the Federal University of Espírito Santo (PPGDIR- UFES), since, from the constitutional point of view, it sought to analyze and extract the full potential of the process organization techniques provided for in art. 357, of CPC/15, verifying the adequacy and efficiency of its application, through procedural adaptability, transporting them to other phases and type of procedures. In order to do so, we sought to demonstrate the current ideological conception that marks the Brazilian civil procedural system, of maximizing constitutional values, valuing the autonomy of the will, contradictory and seeking for broad access to justice. Then, we tried to identify the process organization techniques inserted in the aforementioned legal provision and what the objective of each one is. Considering the potential of each of the techniques identified, it was engendered to verify the possibility of adaptability of the procedure for the transport of the aforementioned techniques initially foreseen only in the common procedure for the other phases and procedures. Then, some possibilities for managing the techniques were presented, as well as their respective benefits, both as an indicative guide for lawyers to "organize" the process from its inception, and in the complementation, completion and optimization of the appeal, executive and procedural phases. special inventory and autonomous evidentiary action. Finally, the final conclusions of the research were exposed.